Glutamatergic Contribution to Probabilistic Reasoning and Jumping to Conclusions in Schizophrenia: A Double-Blind, Randomized Experimental Trial - Strube, Wolfgang; Marshall, Louise; Quattrocchi, Graziella; Little, Simon; Cimpianu, Camelia Lucia; Ulbrich, Miriam; Schneider-Axmann, Thomas; Falkai, Peter; Hasan, Alkomiet; Bestmann, Sven (Biological psychiatry (1969), 2020)
Impaired probabilistic reasoning and the jumping-to-conclusions reasoning bias are hallmark features of schizophrenia (SCZ), yet the neuropharmacological basis of these deficits remains unclear. Here we tested the hypothesis that glutamatergic neurotransmission specifically contributes to jumping to conclusions and impaired probabilistic reasoning in SCZ. A total of 192 healthy participants received either NMDA receptor agonists/antagonists (D-cycloserine/dextromethorphan), dopamine type 2 receptor agonists/antagonists (bromocriptine/haloperidol), or placebo in a randomized, double-blind, between-subjects design. In addition, we tested 32 healthy control participants matched to 32 psychotic inpatients with SCZ—a state associated with compromised probabilistic reasoning due to reduced glutamatergic neurotransmission. All experiments employed two versions of a probabilistic reasoning (beads) task, which required participants to either sample individual amounts of sensory information to infer correct decisions or provide explicit probability estimates for presented sensory information. Our task instantiations assessed both information sampling and explicit probability estimates in different probabilistic contexts (easy vs. difficult conditions) and changing sensory information through random transitions among easy, difficult, and ambiguous trial types. Following administration of D-cycloserine, haloperidol, and bromocriptine, healthy participants displayed data-gathering behavior that was normal compared with placebo and was adequate in the context of all employed task conditions and trial level difficulties. However, healthy participants receiving dextromethorphan displayed a jumping-to-conclusions bias, abnormally increased probability estimates, and overweighting of sensory information. These effects were mirrored in patients with SCZ performing the same versions of the beads task. Our findings provide novel neuropharmacological evidence linking reduced glutamatergic neurotransmission to impaired information sampling and to disrupted probabilistic reasoning, namely to overweighting of sensory evidence, in patients with SCZ.